Molecular amorphous glasses toward large azomethine crystals with aggregation-induced emission1. (27th August 2015) - Marin, Luminita; van der Lee, Arie; Shova, Sergiu; Arvinte, Adina; Barboiu, Mihail
<x xml:space="preserve">Abstract</x> Imine compounds containing rigid cores and soft aliphatic tails have been designed to generate molecular glasses and large crystals displaying aggregation-induced emission, which makes them interesting candidates for optoelectronic applications.